PENERAPAN MEDIA GAME EDUKASI BERBASIS WORDWALL (GAULL) TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA PESERTA DIDIK KELAS IV SD - Komang Yudi Ardika; Dayu Rika Perdana; Siti Nuraini; Muhammad Nurwahidin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study focused on the poor learning results of Pancasila pupils at SDN 5 Metro Timur. This study sought to ascertain how Wordwall-based Educational Games (GAULL) affected fourth-grade elementary school pupils' learning results in Pancasila education. This study employed a non-equivalent control group design and a quasi-experimental methodology. Purposive sampling was used to choose 51 fourth-grade pupils from classes IVA and IVB for the research sample. Tests and non-tests were employed in data collection methods. Normality and homogeneity tests were employed in the required data analysis test. Simple linear regression tests were used to analyze the data. Wordwall-based Educational Game Media (GAULL) had an impact on fourth-grade elementary school students' Pancasila education learning outcomes of 61.5% with a significance value of 0.000 di bawah 0.05, according to the regression test findings. This indicates that Ha was accepted and Ho was rejected.